Aluminum-Lithium Alloys : Processing, Properties, and Applications - Prasad, N. Eswara (Elsevier Science, 2014)
Because lithium is the least dense elemental metal, materials scientists and engineers have been working for decades to develop a commercially viable aluminum-lithium (Al-Li) alloy that would be even lighter and stiffer than other aluminum alloys. The first two generations of Al-Li alloys tended to suffer from several problems, including poor ductility and fracture toughness; unreliable properties, fatigue and fracture resistance; and unreliable corrosion resistance. Now, new third generation Al-Li alloys with significantly reduced lithium content and other improvements are promising a revi.